2009
DOI: 10.1017/s1431927609095828
|View full text |Cite
|
Sign up to set email alerts
|

TEM Characterization of Crept and Irradiated Nano-structured Ferritic Alloys

Abstract: The past ten years or so have seen the development of an exciting new class of mechanically alloyed (MA) nano-structured ferritic alloys (NFA) with outstanding mechanical properties that are mostly due to the presence of high concentrations (>10 23 m -3 ) of Ti-, Y-, and O-enriched nano-clusters (NC). Because NC may promote point defect recombination and trap transmutation-produced He in small clusters, NFA have the potential to be highly resistant to radiation damage in fission and fusion environments [1,2], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…These methods minimize diffraction contrast and in combination provide the information needed to investigate the chemical evolution of the particles after irradiation. Only very few reports have been found that apply these advanced techniques to accomplish such analyses [13,28,44]. Some authors use Fe EFTEM maps to visualize the nanoparticles and APT to study their chemical evolution because attaining reliable Y EFTEM maps is a challenging task due to the locations of its three electron energy loss edges [13,44].…”
Section: Stability Of Secondary Phases After Irradiation 3231 Y-rmentioning
confidence: 99%
“…These methods minimize diffraction contrast and in combination provide the information needed to investigate the chemical evolution of the particles after irradiation. Only very few reports have been found that apply these advanced techniques to accomplish such analyses [13,28,44]. Some authors use Fe EFTEM maps to visualize the nanoparticles and APT to study their chemical evolution because attaining reliable Y EFTEM maps is a challenging task due to the locations of its three electron energy loss edges [13,44].…”
Section: Stability Of Secondary Phases After Irradiation 3231 Y-rmentioning
confidence: 99%
“…These NFA materials, such as the 14YWT alloy studied here, have a complex non-equilibrium microstructure produced by mechanical alloying and extrusion. Previous work [9][10][11][12][13] has indicated the microstructure consists of a ferritic matrix with a grain size of $100-500 nm, with strong enrichment of Cr and W solutes at the grain boundaries over a width of $1.5 nm [14]. Titanium oxycarbonitride (Ti(O,C,N)) precipitates of $20-75 nm size are also found in the microstructure.…”
Section: Introductionmentioning
confidence: 97%